Two-Year Outcomes of Patients Treated With Aliskiren Under Clinical Practice Conditions: Non-Interventional Prospective Study - Zeymer, Uwe; Dechend, Ralf; Riemer, Thomas; Deeg, Evelin; Senges, Jochen; Pittrow, David; Schmieder, Roland (Journal of Clinical Hypertension, 2016)
The authors investigated the long-term effectiveness and safety of aliskiren (ALIS) with particular attention on its association with dual blockade of the renin-angiotensin system (RAS). The open, prospective 3A Registry (N=8723) in Germany assigned patients in a 4:1:1 ratio to ALIS, angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs), or non-RAS drugs. Patients taking ALIS compared with those taking ACE inhibitors/ARBs or non-RAS had more comorbidities and risk factors, were taking more antihypertensive agents, and had higher blood pressure (BP) values at entry. At 2 years, BP reduction from baseline was similar in all groups (mean, -20.5/-9.9 mm Hg). A total of 2.3% of patients died, 0.5% had myocardial infarction, 0.6% had stroke, 2.9% were hospitalized, and 5.5% had any event (not significant between groups). ALIS alone or combined with another RAS inhibitor was well tolerated and effective in lowering BP in typical unselected patients with hypertension. Given the methodical limitations of the design, the study cannot be used to confirm or refute safety concerns for dual RAS blockade as suggested by the Aliskiren Trial in Type 2 Diabetes Using Cardio-Renal Endpoints (ALTITUDE) trial.
EVALuna2:3893